Pemasaran Saham-Saham Syari’ah oleh Broker Saham di Kota Banda Aceh - Zikri Mahyar Ray (STAI Al-Washliyah Banda Aceh, 2020)
Stock brokers are instrumental in marketing stocks especially in increasing their promotion of Shariah stocks so that investors want to trade in Shariah stocks. Understanding of Shari'ah shares should continue to be disseminated within the community, so that the public understands the differences of conventional stock and Shari'ah shares. The purpose of this research is to know how the stock broker strategy in Banda Aceh City in promoting syari'ah shares as well as its influence in purchasing syari'ah stocks and to know the barriers and challenges of stock brokers when promoting the shares of sharia in the company securities in the city of Banda Aceh. This research method is qualitative with descriptive analysis. This research type is descriptive with qualitative approach, using instrument of observation data and interview. While data analysis by way of data reduction, data presentation and conclusion. The results of this study found that stock brokers in Banda Aceh City in marketing Shariah stocks using education and socialization to the public by holding seminars on syari'ah capital market. The effect of the broker's promotion on the purchase of Shari'ah shares is the increasing number of people who know about the syariah capital market. In marketing sharia stocks there are obstacles and challenges because in transacting shares in the capital market stock brokers in the city of Banda Aceh there are two points of view. First, brokers are considering the religious aspect when promoting stocks. Second, stock brokers who do not consider the religious aspect of promoting their shares. Then plus there are people who still consider the same between the shares of shari'ah with conventional shares.